2008
DOI: 10.1016/j.neuroimage.2008.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Functional grouping and cortical–subcortical interactions in emotion: A meta-analysis of neuroimaging studies

Abstract: We performed an updated quantitative meta-analysis of 162 neuroimaging studies of emotion using a novel multi-level kernel-based approach, focusing on locating brain regions consistently activated in emotional tasks and their functional organization into distributed functional groups, independent of semantically defined emotion category labels (e.g., "anger," "fear"). Such brain-based analyses are critical if our ways of labeling emotions are to be evaluated and revised based on consistency with brain data. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

83
914
3
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 981 publications
(1,004 citation statements)
references
References 171 publications
(183 reference statements)
83
914
3
4
Order By: Relevance
“…This is an agreement with other studies that there is decrease in brain's complexity during emotion processing due to the dysfunction in the neural circuits (Adolphs et al, 1996;Lawrence et al, 2007). Recent evidence points to neuropathological changes in PD in many brain areas which are assumed to play key roles in emotion processing (Kober et al, 2008). These include limbic structures such as the amygdala, and the ventral striatum, which is centrally located within the basal ganglia's Emotional state classification in PD 26 limbic loop.…”
Section: Choosing Of Svm Kernelssupporting
confidence: 89%
“…This is an agreement with other studies that there is decrease in brain's complexity during emotion processing due to the dysfunction in the neural circuits (Adolphs et al, 1996;Lawrence et al, 2007). Recent evidence points to neuropathological changes in PD in many brain areas which are assumed to play key roles in emotion processing (Kober et al, 2008). These include limbic structures such as the amygdala, and the ventral striatum, which is centrally located within the basal ganglia's Emotional state classification in PD 26 limbic loop.…”
Section: Choosing Of Svm Kernelssupporting
confidence: 89%
“…This area has consistently been associated with emotion processing (Kober et al, 2008;Lindquist et al, 2012;Phan et al, 2002;Vytal & Hamann, 2010), also in the music domain (Khalfa et al, 2005). The cluster overlapped bilaterally with a cluster found by Williams et al (2006) during the explicit processing of fearful faces.…”
Section: Explicit Vs Implicitmentioning
confidence: 63%
“…Metaanalyses of fMRI studies of emotion have indeed shown the involvement of large brain networks related to perceptual, motor, or cognitive processes. [40,41] Barrett et al [31] outline the most prominent structures that have been identified as central during the evaluation of the emotional significance of stimulus events and the processes that lead to the emergence of the emotional experience. The core of the system involved in the translation of external and internal events to the affective state is a set of neural structures in the ventral portion of the brain: medial temporal lobe (including the amygdala, insula, and striatum), orbitofrontal cortex (OFC), and ventromedial prefrontal cortex (VMPFC).…”
Section: Affect In the Brainmentioning
confidence: 99%